Graphical Representations of E-Achievability Region for Identification and Secret-Key - Ter-Vardanyan, Lilit A. (Mathematical Problems of Computer Science, 2021)
In this paper we represent the computations of theoretical results, obtained in [1], on the example of binary symmetric channel. The computations and graphical representations are realized using the “Advanced Inftheo” module, created in 2015 [2, 3] for R environment.